2020
DOI: 10.1634/theoncologist.2020-0028
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Hyperfractionated Dosing of Lutetium-177–Labeled Antiprostate-Specific Membrane Antigen Monoclonal Antibody J591 (177Lu-J591) for Metastatic Castration-Resistant Prostate Cancer

Abstract: Lessons Learned Hyperfractionation of lutetium‐177 (177Lu)‐J591 for patients with metastatic castration‐resistant prostate cancer did not appear to have any additional advantage over the single dose 177Lu‐J591 or fractionated two‐dose 177Lu‐J591 therapy. Definite conclusions were challenging because of the small sample size of this study, and so further studies are needed to evaluate the viability of the hypothesis. On the basis of available data, a registration study of 177Lu‐J591 (also known as TLX591) is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…We performed a post hoc analysis of all subjects who were included in our phase I/II β‐radiation emitting PSMA‐TRT studies with enrollment during the period between July 2002 and October 2018 1–4,6,7 . Key eligibility criteria included prospective mCRPC by Prostate Cancer Working Group criteria with no available standard therapies or refusal of standard therapies and intact performance status and organ function as previously described.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We performed a post hoc analysis of all subjects who were included in our phase I/II β‐radiation emitting PSMA‐TRT studies with enrollment during the period between July 2002 and October 2018 1–4,6,7 . Key eligibility criteria included prospective mCRPC by Prostate Cancer Working Group criteria with no available standard therapies or refusal of standard therapies and intact performance status and organ function as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to radionuclide activity for pretreatment imaging, 5 mCi of 111 In were used. As 177 Lu is a therapeutic radionuclide with both β and γ emission, other than those that were imaged with 111 In or 68 Ga, there was no pretreatment imaging specifically using 177 Lu; rather images used for initial treatment served as baseline imaging 1–4,6,7 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After phase I and II single-dose studies of 177 Lu-J591 demonstrated safety and efficacy with dose-response, and dose fractionation of 177 Lu-J591 permitted higher cumulative dose administration with less myelosuppression per similar cumulative dose in single-dose studies, the idea of the hyperfractionation of 177 Lu-J591 emerged [8][9][11][12][13]. The researchers hypothesized that the hyperfractionation of 177 Lu-J591 will allow the safer administration of a higher cumulative dose with less potential toxicity.…”
Section: Pilot Study Of the Hyperfractionated Dosing Of 177 Lu-j591mentioning
confidence: 99%